A hollow carbon ball loaded MoS3 magnesium ion battery positive electrode material and preparation method thereof
The a-MoS3/HCS composite material prepared through self-assembly and etching reactions solves the problem of poor magnesium storage capacity and diffusion kinetics of the positive electrode material of magnesium ion battery, and achieves high capacity, excellent magnification and good cycling performance.
Patent Information
- Application Number
- CN202410557239.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-05-07
AI Technical Summary
The cathode material of magnesium ion battery has poor performance in magnesium storage capacity and diffusion kinetics, resulting in a large gap in actual and theoretical capacity, and insufficient rate performance and cycle life.
SiO2@RF was synthesized by self-assembly and annealed, solid carbon sphere SiO2@C was formed, and then hollow carbon spheres were loaded with HCS through etching reaction, and finally acid precipitation reaction was carried out with the molybdenum source to prepare a-MoS3/HCS composite material.
This method significantly improves the magnesium storage performance of the positive electrode material of magnesium ion battery, has high reversible capacity, excellent magnification ability and good cycle stability.
Smart Images

Figure CN118231628B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium ion battery materials, and in particular to a magnesium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] As a rechargeable energy storage device, lithium-ion batteries (LIBs) have been widely used in high-tech emerging industries such as portable electronics, electric vehicles, and smart manufacturing. Although LIBs are the most successful energy storage devices developed to date, they still face many challenges such as limited lithium resources, high cost, safety risks, and insufficient energy density. Among the many alternatives, magnesium-ion batteries (MIBs) are a very promising electrochemical energy storage device. Metallic Mg is a chemically stable and abundant metal with a higher theoretical volumetric capacity than lithium (3833 mAh cm -3 ) and a lower reduction potential (-2.37 V relative to standard hydrogen electrode). More importantly, unlike metallic Li, metallic Mg is not prone to dendrite formation during the reversible electrochemical deposition / dissolution process, making it safer as a battery material. However, a key obstacle to the success of high-performance MIBs is the slow Mg degradation of the cathode material. 2+ storage kinetics, which results in a large gap between actual and theoretical magnesium storage capacity.
[0003] The use of magnesium metal anodes greatly broadens the potential choices of cathode materials, as more magnesium-deficient cathode materials can be selected. So far, research on magnesium-ion batteries is still in its early stages. Magnesium-ion batteries face two major obstacles in practical applications: 1) the diffusion kinetics of magnesium ions in cathode materials are slow; 2) divalent magnesium ions have a high polarization ability, resulting in incompatibility between cathode materials and electrolytes.
[0004] At present, the existing 2H phase MoS2 has fewer sulfur defects and fewer active sites, which cannot improve the magnesium storage capacity. In addition, the structure of crystalline MoS2 determines the Mg 2+ The locations for intercalation and deintercalation are limited, and the actual capacity is restricted by many factors, such as crystal orientation, phase transition, exposed crystal facets, and structural stability, making it impossible to extend the cycle life.
[0005] Therefore, there is an urgent need for a magnesium ion battery positive electrode material and a preparation method thereof that can achieve a high diffusion rate, a high magnesium storage capacity, and a high rate performance. Summary of the invention
[0006] In order to overcome the above-mentioned defects in the prior art such as low magnesium storage capacity, slow diffusion kinetics, and limited active sites, the present invention provides a magnesium ion battery positive electrode material and a preparation method thereof, which solves the problems of poor rate performance, capacity attenuation and short service life in the prior art.
[0007] In order to overcome the above defects, the present invention provides the following technical solutions to solve the above technical problems:
[0008] First aspect:
[0009] The present invention discloses a method for preparing a positive electrode material for a magnesium ion battery, which is characterized in that the specific steps include:
[0010] (1) SiO2@RF is synthesized by self-assembly of silicic acid and resin, and then solid carbon spheres SiO2@C are obtained after annealing;
[0011] (2) The solid carbon sphere SiO2@C is etched with inorganic acid / inorganic base A to obtain a hollow carbon sphere supported phase (HCS);
[0012] (3) The molybdenum source and the supported phase are stirred and subjected to an acid precipitation reaction with an inorganic acid B to obtain the target product (a-MoS3 / HCS).
[0013] Preferably, at least one of the following conditions is met in step (1):
[0014] Wherein, the silicic acid comprises tetraethyl orthosilicate;
[0015] Wherein, the resin comprises resorcinol and formaldehyde;
[0016] Wherein, the temperature of the annealing treatment is 600-900°C;
[0017] The average size of the hollow carbon spheres SiO2@RF is 200-400 nm.
[0018] Preferably, step (2) satisfies at least one of the following conditions:
[0019] Wherein, the inorganic acid / inorganic base includes hydrofluoric acid and sodium hydroxide;
[0020] Wherein, the concentration of the inorganic acid A is 10-20%
[0021] Preferably, the etching reaction in step (2) is 4HF+SiO2=SiF4+2H2O
[0022] Preferably, the loading phase further comprises a dispersing operation before use.
[0023] Preferably, the dispersion is carried out under ultrasonic conditions;
[0024] Wherein, the power of the ultrasonic wave is 400W
[0025] Wherein, the ultrasonic time is 1 to 3 hours.
[0026] Preferably, step (3) satisfies at least one of the following conditions:
[0027] Wherein, the molybdenum source includes ammonium polythiomolybdate, such as ammonium tetrathiomolybdate;
[0028] Wherein, the stirring time is 1 to 3 hours;
[0029] Wherein, the stirring speed is 500-600 rpm;
[0030] Wherein, the inorganic acid B includes hydrochloric acid, oxalic acid, glacial acetic acid, and sulfuric acid;
[0031] Wherein, the concentration of the inorganic acid is 1 mol / L
[0032] Wherein, the acid precipitation reaction is adjusted to a pH of 1.5 to 2.5.
[0033] Preferably, step (3) further comprises centrifugation and / or drying operations.
[0034] Preferably, the centrifugation operation comprises: centrifuging with deionized water for 2 to 4 times; and then centrifuging with anhydrous ethanol for 2 to 4 times.
[0035] The drying operation includes: vacuum drying at 50-70° C., and the vacuum pressure is -80 kPa.
[0036] The present invention also provides a magnesium ion battery positive electrode material, characterized in that it is prepared by any one of the above methods for preparing the magnesium ion battery positive electrode material.
[0037] Second aspect:
[0038] In the present invention, hollow carbon nanospheres are introduced to effectively prevent the agglomeration of MoS3 particles and improve the Mg 2+ Diffusion kinetics and electron transport efficiency.
[0039] The introduction of hollow carbon nanospheres into amorphous MoS3 through etching reaction solves the inherent low conductivity problem of MoS3 and promotes the kinetics of redox reactions. The amorphous characteristics break the limitation of fixed lattice spacing, introduce a large number of defects, and increase the number of anionic redox centers.
[0040] The hollow structure of carbon nanospheres can serve as a growth template for molybdenum trisulfide loading, effectively alleviating the large volume expansion of MoS3 during the cycle, inhibiting the pulverization of MoS3 and the dissolution of polysulfides, and maximizing the utilization of active materials.
[0041] In the acid precipitation process of the present invention, a-MoS3 can be anchored on the surface of HCS through strong bonds with functional groups of molybdenum and carbon (Mo-C).
[0042] In the present invention, under the condition of quantitative hydrochloric acid, the generated MoS3 will successfully grow on the inner cavity and outer shell of HCS, thereby forming an a-MoS3 / HCS composite material.
[0043] Compared with the prior art, the present invention has the following technical effects:
[0044] (1) The present invention provides a positive electrode material for magnesium ion batteries and a preparation method thereof. A well-designed carbon hollow nanosphere-loaded MoS3 positive electrode material (a-MoS3 / HCS) is prepared by amorphization and anion-enriched strategies. As a new positive electrode material for magnesium ion batteries, a-MoS3 / HCS exhibits significant magnesium storage performance and has an ultra-high reversible capacity (at 0.1Ag -1 472.5mAh g -1 ), excellent rate capability (even at 5A g -1 The reversible capacity remains at 87.4 mAh g -1 ) and acceptable long-term cycling stability (at 2Ag -1 The cycle life is 300 cycles).
[0045] (2) The present invention provides a magnesium ion battery positive electrode material and a preparation method thereof. The preparation process is simple. Even when the prepared product is cycled at a relatively low temperature of 0°C, a-MoS3 / HCS can still work and show satisfactory cycle performance. Moreover, in the application field, in addition to button batteries, soft-pack batteries are also assembled, which can easily drive various electronic devices, demonstrating its practical application in magnesium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are embodiments and comparative examples of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0047] Figure 1 TEM image of SiO2@RF measured using this embodiment;
[0048] Figure 2 The SEM, TEM, and HRTEM images of 2H-MoS2 / HCS prepared in Example 1 are shown;
[0049] Figure 3 is a SEM image of a-MoS3 / HCS prepared using Example 1;
[0050] Figure 4 TEM and HRTEM images of a-MoS3 / HCS prepared in Example 1;
[0051] Figure 5 The XRD diagram of a-MoS3 / HCS prepared in Example 1; The XRD diagram of 2H-MoS2 / HCS prepared in Comparative Example 1;
[0052] Figure 6 The Raman image of a-MoS3 / HCS prepared using Example 1; the Raman image of 2H-MoS2 / HCS prepared using Comparative Example 1;
[0053] Figure 7 The results of the battery assembled using 1a-MoS3 / HCS of this embodiment and 2H-MoS2 / HCS prepared in comparative example 1 at different current densities (0.05Ag -1 , 0.1Ag -1 , 0.2A g -1 , 0.5A g -1 , 1Ag -1 , 2Ag -1 , 3A g -1 , 5A g -1 )’s rate performance diagram;
[0054] Figure 8 The battery assembled with a-MoS3 / HCS prepared in Example 1 and the battery assembled with 2H-MoS2 / HCS prepared in Comparative Example 1 were tested at 1A g -1 Cycling performance diagram after 200 cycles at a current density of . DETAILED DESCRIPTION
[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] The raw materials used in the present invention are all commercially available.
[0057] Example 1
[0058] (1) 6 mL of tetraethyl orthosilicate, 0.4 g of resorcinol, and 0.56 mL of formaldehyde were used as reaction materials to synthesize SiO2@RF by self-assembly technology. Then, by annealing at a high temperature of 700°C, uniform solid carbon spheres (SiO2@C) with an average size of 300 nm were obtained for later use.
[0059] (2) The solid carbon sphere SiO2@C is etched with hydrofluoric acid to obtain a hollow carbon sphere supported phase (HCS);
[0060] (3) Under ultrasonic conditions with a power of 400 W, 10 mg of hollow carbon spheres (HCS) were dispersed in 25 mL of deionized water for 2 hours to obtain a uniform dispersed solution; at the same time, 70 mg of (NH4)2MoS4 was dissolved in 20 mL of deionized water and stirred for 2 hours. After the above two solutions were mixed and stirred for 2 hours, a dilute hydrochloric acid solution was gradually added to the mixture to adjust the pH to 2. Finally, the mixture was centrifuged and washed three times with 95% ethanol solution, and then dried in a vacuum oven at 60°C overnight to obtain a magnesium ion battery positive electrode material, namely a black a-MoS3 / HCS composite material.
[0061] Example 2
[0062] Compared with Example 1, the difference is that the mass ratio of HCS to (NH4)2MoS4 is different, and other conditions are the same. The specific operation is as follows:
[0063] (1) 6 mL of silicic acid, 0.4 g of resorcinol, and 0.56 mL of formaldehyde were used as reaction materials and synthesized by self-assembly technology. Then, uniform solid carbon spheres (SiO2@C) with an average size of 300 nm were obtained by annealing at 700°C for later use.
[0064] (2) etching SiO2@C with hydrofluoric acid to obtain a hollow carbon sphere supported phase (HCS);
[0065] (3) Under ultrasonic conditions with a power of 400 W, 10 mg of HCS was dispersed in 25 mL of deionized water for 2 hours to obtain a uniform dispersed solution; at the same time, 80 mg of (NH4)2MoS4 was dissolved in 20 mL of deionized water and stirred for 2 hours. After the above two solutions were mixed and stirred for 2 hours, a dilute hydrochloric acid solution was gradually added to the mixture to adjust the pH to 2. Finally, the mixture was centrifuged and washed three times with a 95% ethanol solution and then dried in a vacuum oven at 60°C overnight to obtain a magnesium ion battery positive electrode material, namely a black a-MoS3 / HCS composite material.
[0066] Example 3
[0067] Compared with Example 1, the difference is that the annealing temperature is 800 degrees Celsius, and other conditions are the same. The specific operations are as follows:
[0068] (1) 6 mL of silicic acid, 0.4 g of resorcinol, and 0.56 mL of formaldehyde were used as reaction materials and synthesized by self-assembly technology. Then, uniform solid carbon spheres (SiO2@C) with an average size of 300 nm were obtained by annealing at 800°C for later use.
[0069] (2) etching SiO2@C with hydrofluoric acid to obtain a hollow carbon sphere supported phase (HCS);
[0070] (3) Under ultrasonic conditions with a power of 400 W, 10 mg of HCS was dispersed in 25 mL of deionized water for 2 hours to obtain a uniform dispersed solution; at the same time, 70 mg of (NH4)2MoS4 was dissolved in 20 mL of deionized water and stirred for 2 hours. After the above two solutions were mixed and stirred for 2 hours, a dilute hydrochloric acid solution was gradually added to the mixture to adjust the pH to 2. Finally, the mixture was centrifuged and washed three times with a 95% ethanol solution and then dried in a vacuum oven at 60°C overnight to obtain a magnesium ion battery positive electrode material, namely a black a-MoS3 / HCS composite material.
[0071] Comparative Example 1
[0072] (1) 10 mg of HCS was ultrasonically dispersed in 10 mL of ethanol and 5 mL of deionized water, and then a 1 M dilute hydrochloric acid solution was added to the above dispersion to adjust the pH to 3 to obtain a dispersion for later use.
[0073] (2) 0.2 mg Na2MoO4·2H2O and 1.0 g CS(NH2)2 were dissolved in 20 mL deionized water and stirred for 1 hour. Then, 0.15 g ascorbic acid was added and stirred for 5 minutes to obtain a base phase for later use.
[0074] (3) The base phase was slowly poured into the dispersion and stirred for 3 h to obtain a mixed solution, which was then transferred into a 75 mL polytetrafluoroethylene-lined autoclave and then subjected to solvothermal treatment at 190 °C for 20 h. Finally, the magnesium ion battery cathode material, i.e., black 2H-MoS2 / HCS composite material, was obtained by centrifugation with ethanol and deionized water several times and vacuum drying at 60 °C overnight.
[0075] In the embodiment of the present invention, hollow carbon spheres are used as the loading phase, and high-capacity MoS3 is successfully loaded on the hollow carbon spheres to obtain a new cathode material a-MoS3 / HCS, which is compared and performance analyzed with a similar comparative example 2H-MoS2 / HCS.
[0076] according to Figure 1 It can be seen that the SiO2@C prepared in Example 1 of the present invention is a solid carbon sphere, and the diameter of the a-MoS3 / HCS hollow carbon sphere obtained after calcination and etching is 200-400 nm.
[0077] according to Figure 2 It can be seen that the diameter of 2H-MoS2 / HCS prepared in Comparative Example 1 of the present invention is about 300nm. The TEM image clearly shows that some thin and curved MoS2 nanosheets with an average size of 20nm are evenly anchored on the inner and outer surfaces of HCS; the HRTEM image shows a wide lattice spacing of 0.62nm.
[0078] according to Figure 3 It can be seen that the a-MoS3 / HCS prepared by the present invention has a uniformly dispersed hollow spherical structure with a smooth surface and an average diameter of 300nm.
[0079] according to Figure 4 It can be seen that some MoS3 layers in the a-MoS3 / HCS prepared in Example 1 of the present invention are wrapped on the inner and outer surfaces of HCS; the enlarged HRTEM image shows that a-MoS3 / HCS has no obvious lattice fringes, revealing the amorphous characteristics of MoS3.
[0080] according to Figure 5 It can be seen that the 2H-MoS2 / HCS prepared in Comparative Example 1 of the present invention has three diffraction peaks of 2H-MoS2 at approximately 14.4°, 32.7° and 58.3°, while the inconspicuous diffraction peaks of a-MoS3 / HCS show the amorphous nature of MoS3.
[0081] according to Figure 6 It can be seen that the a-MoS3 / HCS prepared in Example 1 of the present invention is located at 277cm -1 and 347cm -1 The two scattering peaks at 276 cm-1 are attributed to the characteristic vibration modes of MoS3, while the 2H-MoS2 / HCS prepared in Comparative Example 1 is located at 276 cm-1. -1 , 387cm -1 and 413cm -1 The three characteristic peaks are attributed to the typical E of 2H-MoS2 1g , E 2g and A 1g Vibration mode.
[0082] according to Figure 7 It can be seen that the a-MoS3 / HCS prepared in Example 1 of the present invention has an ultra-high reversible capacity (at 0.1Ag -1 472.5mAh g -1 ), excellent rate capability (even at 5A g -1 The specific capacity is still 87.4 mAh g -1 ), which is significantly better than the 2H-MoS2 / HCS prepared in Comparative Example 1.
[0083] according to Figure 8 It can be seen that Example 1 of the present invention has ideal cycle stability, and the discharge capacity is significantly higher than that of the crystalline 2H-MoS2 / HCS prepared in Comparative Example 1. -1 At the current density, the cycle life is 200 times.
[0084] The present invention prepares a well-designed carbon hollow nanosphere-loaded MoS3 positive electrode material (a-MoS3 / HCS) through amorphization and anion-rich strategies. As a new positive electrode material for magnesium ion batteries, a-MoS3 / HCS exhibits significant magnesium storage performance.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode material for a magnesium ion battery, characterized in that: The specific steps include: (1) Resorcinol, formaldehyde and tetraethyl orthosilicate were self-assembled to synthesize SiO2@RF, and then solid carbon spheres SiO2@C were obtained after annealing. (2) The solid carbon sphere SiO2@C is etched with inorganic acid / inorganic base A to obtain a hollow carbon sphere supported phase (HCS); (3) The molybdenum source and the hollow carbon sphere support phase are stirred in water and subjected to an acid precipitation reaction with an inorganic acid B to obtain the target product (a-MoS3 / HCS).
2. The method for preparing a positive electrode material for a magnesium ion battery according to claim 1, characterized in that: At least one of the following conditions is met in step (1): The temperature of the annealing treatment is 600-900°C; The average size of the hollow carbon sphere supporting phase is 200-300 nm.
3. The method for preparing a positive electrode material for a magnesium ion battery according to claim 1, characterized in that: Step (2) satisfies at least one of the following conditions: The inorganic acid includes hydrofluoric acid; The inorganic base includes sodium hydroxide; The concentration of the inorganic acid A is 10-20%.
4. The method for preparing a positive electrode material for a magnesium ion battery according to claim 1, characterized in that: The etching reaction in step (2) is 4HF+SiO2=SiF4+2H2O.
5. The method for preparing a positive electrode material for a magnesium ion battery according to any one of claims 1 to 4, characterized in that: The hollow carbon sphere supporting phase further includes a dispersion operation before use.
6. The method for preparing the positive electrode material for magnesium ion battery according to claim 5, characterized in that: The dispersing condition is to disperse under ultrasonic conditions; The power of the ultrasonic wave is 400W; The ultrasonic time is 1 to 3 hours.
7. The method for preparing a positive electrode material for a magnesium ion battery according to claim 1, characterized in that: Step (3) satisfies at least one of the following conditions: The molybdenum source includes ammonium tetrathiomolybdate; The mass ratio of the molybdenum source to the hollow carbon sphere support phase is 1:(6-8); The mass concentration of the molybdenum source is 0.2-0.6 g / L; The stirring time is 1 to 3 hours; The stirring speed is 500-600 rpm; The inorganic acid B includes hydrochloric acid, oxalic acid, glacial acetic acid, and sulfuric acid; The concentration of the inorganic acid is 1 mol / L; The acid precipitation reaction is adjusted to a pH of 1.5 to 2.
5.
8. The method for preparing a positive electrode material for a magnesium ion battery according to claim 1, characterized in that: Step (3) further includes centrifugation and / or drying operations.
9. The method for preparing a positive electrode material for a magnesium ion battery according to claim 8, characterized in that: The centrifugal operation includes: centrifuging with deionized water for 2 to 4 times; and then centrifuging with anhydrous ethanol for 2 to 4 times; The drying operation includes: vacuum drying at 50-70° C., and the vacuum pressure is -80 kPa.
10. A magnesium ion battery positive electrode material, characterized in that: The magnesium ion battery positive electrode material is prepared according to the method for preparing the magnesium ion battery positive electrode material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Carbon-coated iron silicate hollow-structure compound and preparation method thereof
CN108232167A
Hollow carbon sphere / molybdenum disulfide bipolar composite material and preparation method and application thereof
CN110137475A